The mirror syndrome as a manifestation of angiogenic imbalance, a propos of a case - Lacunza Paredes, Rommel Omar (2018)
The mirror syndrome is a rare obstetric condition whose classical triad is fetal hydrops, generalized maternal edema and placentomegaly. We present the case of a 25 weeks pregnant woman with diagnosis of fetal hydrops due to severe anemia presenting criteria of severe preeclampsia with fetal death, in the context of mirror syndrome. We review the literature with emphasis on anti-angiogenesis as the pathophysiological origin of the disease.